Caracterização do tratamento medicamentoso com estatinas em unidade básica de saúde - Bonfim, Mariana R. [UNESP]; Oliveira, Acary S. B.; Amaral, Sandra Lia do [UNESP]; Monteiro, Henrique Luiz [UNESP] (My University, 2013)
Study Model: Retrospective study. Study Objective: To characterize statin treatment management due to lipid alterations and side effects throughout statin treatment in basic healthcare unit. Methods: Medical reports of women from a basic healthcare unit were analyzed, obtaining: disease presence, regular medication prescription, statin type and dosage, biochemical exams results, musculoskeletal complaints, and statin use cessation, going back the information until the medical consultation of first prescription. Results: Prescribed statins were Simvastatin and Atorvastatin at low doses (10-20 mg). Dose (48,4%) and/or type (25,4%) alterations occurred for lipid profile adequacy. Lipid levels were reduced without creatine kinase elevation. Treatment withdrawn (30,6%) was mainly due to their own decision (74%), which was strongly associated with records of musculoskeletal complaints (Odds Ratio: 6,40[1,53-26,78]). Conclusion: Statin treatment was effective in reducing serum lipid levels and self-reported pain was underestimated, characterizing the major limiting factor for treatment adherence.
Characterization of statin treatment in basic healthcare unit
Keywords: Dyslipidemias; HMG-CoA; Medication therapy management; Public health; Statins; atorvastatin; creatine kinase; lipid; simvastatin; consultation; creatine kinase blood level; disease association; disorders of lipid and lipoprotein metabolism; drug withdrawal; female; health care facility; human; lipid analysis; lipid blood level; low drug dose; medical information; musculoskeletal disease; prescription; retrospective study